2013
DOI: 10.1179/1754762811y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in mitochondrial deafness due to A7445G mutation

Abstract: Individuals with mtDNA-related SNHL should be identified by screening and offered assessment for CI suitability because functional hearing improves after CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…CI outcomes are few and documented in individuals who possess mutations in the TWNK and TWIST1 genes, as well as pathogenic CNVs in the 7p22.1 region. Positive outcomes have been obtained in patients with sensory hearing loss attributed to m.A7445G following CI (Love and Bird, 2013), same results have been observed in individual with AN (case 39) in this study as well. Previous reports have indicated that patients with mutations in ACTG1 gene exhibited satisfactory speech performances after CI (Liu et al, 2019).…”
Section: Presynaptic and Postsynaptic Mechanisms Of Ansupporting
confidence: 88%
“…CI outcomes are few and documented in individuals who possess mutations in the TWNK and TWIST1 genes, as well as pathogenic CNVs in the 7p22.1 region. Positive outcomes have been obtained in patients with sensory hearing loss attributed to m.A7445G following CI (Love and Bird, 2013), same results have been observed in individual with AN (case 39) in this study as well. Previous reports have indicated that patients with mutations in ACTG1 gene exhibited satisfactory speech performances after CI (Liu et al, 2019).…”
Section: Presynaptic and Postsynaptic Mechanisms Of Ansupporting
confidence: 88%
“…Cochlea tissue is rich in mtDNA, which have a high probability of deletion. The deletions in mtDNA in cochlea tissue have been shown to include mtDNA 13162, 10422, 7663, 7436, 4989 and 4977 bp deletions, with the mtDNA CD4977 being the most common in cochlea tissue (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%